Transport properties of lattice fluid with SALR-potential on a simple square lattice - Groda, Yaroslav G.; Lasovsky, Ruslan N. (Journal of the Belarusian State University. Physics, 2021)
The transport properties of the lattice fluid with the attraction interaction between the nearest and repulsion interaction between the next-next-nearest neighbours on the square lattice are investigated. Computer simulation by the Monte Carlo method of the diffusion process in the specified system has been realised. The jump and tracer diffusion coefficients were determined. The dependence of the diffusion coefficients versus the concentration of adparticles and the interaction parameter of the model is investigated. The activation energy of jump and tracer diffusion determined. The possibility of estimating the jump diffusion coefficient of the lattice fluid with competing interactions using the Zhdanov’s relation on the base of information on the equilibrium properties of the system and the diffusion coefficient of a Langmuir (non-interacting) lattice gas is shown. In the future, it is planned to use the obtained results to study transport processes in 3D lattice systems which is suitable for describing the processes of mass or charge transfer in the volumes of solids.